Influence of job satisfaction and demographic factors on organizational commitment among of teachers of federal government girls’ college, zaria, nigeria - Maitama Kura, Kabiru; Abubakar, Ramatu Abdulkareem; Abdullahi, Sani Alhaji; Akpan, Anniete Benson (Journal of Management and Science, 2012)
One of the major concerns of many employers and human resource management practitioners (HRMPs) is to make their employees highly satisfied in order to retain them as well as to make them productive and committed to their organization. Unfortunately, many cases of turnover and poor attitudes to work have been frequently reported by many surveys and news media. One significant reason that the cost of turnover in the secondary school remains high are due to the poor pay, limited promotion opportunities, poor supervision, poor communication among others. The objective of the study was to investigate the influence of job satisfaction and demographic characteristics on organizational commitment among teachers of Federal Government Girls‟ College, Zaria, Nigeria. A cross-sectional survey was conducted on a sample of 52 teaching staff of Federal Government Girls College, Zaria. Correlational and regression analyses techniques were used to analyze the data collected. The study .revealed that (1) there significant positive relationship between job satisfaction and organizational commitment (2) there was a significant positive positive relationship between age and organizational commitment; and (3) there was significant negative relationship between education and organizational commitment Based on the findings, it is recommended that in order to ensure a high level of job satisfaction of teachers there is a need to enhance their salary. This is needed to satisfy the pay need of the teachers and also improve the public image and self esteem of teachers. Teachers‟ working conditions should also be improved also in order to ensure that highly qualified and very experienced teachers are retained in the schools.